TYPE 2 DIABETES MELLITUS: HOW WELL CONTROLLED IN OUR PATIENTS? - Ahmed, Nasir; Jadoon, Shakeel Ahmad; Khan, Raza Muhammad; Duha, Mazahar -ud-; Javed, Mohammed (Journal of Ayub Medical College Abbottabad, 2008)
Background: Type 2 Diabetes mellitus has reached epidemic proportions worldwide and Pakistan is no exception. This study was done to see the glycaemic control of our diabetic patients by estimating Glycosylated haemoglobin & Fasting blood glucose as poor control leads to significant complications causing enormous human suffering & socioeconomic burden. Method: This Cross-sectional study was conducted on Type 2 diabetic patients coming to medical OPD and medical B ward of Ayub Teaching Hospital between March-September 2007 fulfilling the inclusion criteria. Results: Among 100 patients with type 2 diabetes forty two had HbA1c more than 7.5 %, while seventy had fasting blood glucose more than 120 mg/dl. All patients with HbA1c more than 7.5% had increased fasting blood glucose. While thirty out of seventy patients with fasting blood glucose more than 120 mg/dl had HbA1c less than 7.5%. None of the patients with fasting blood glucose less than 120 mg/dl had HbA1c more than 7.5%. Conclusions: Significant number of patients (42%) had poor control of diabetes as revealed by HbA1c, with FBG showing poor control in even more patients, i.e., 70%. However their blood glucose estimation was not frequent enough as required. Blood glucose results can be spuriously high and may lead to frequent change/ increase in the dose of hypoglycaemic medications. This can lead to poor compliance as well as psychological trauma to patients. HbA1c on the other hand is easy to interpret, reflects long term glycaemic control and cost effective. We recommend its more frequent use along with blood glucose for better glycaemic control and decreased chances of complications. Keywords: Glycosylated Haemoglobin, Fasting Blood Glucose, Type 2 Diabetes mellitus